The Effect of Organizational Innovativeness in Enhancing Teacher Innovation in Malaysia’s TVET Sector - Julia, Cliffton; Marinah, Awang (RSIS International, 2025)
This study aims to examine the effect of Organizational Innovativeness, a key dimension of Organizational Culture, on teacher innovation measured as Innovative Work Behaviour (IWB) within Malaysia’s Technical and Vocational Education and Training (TVET) sector. A quantitative approach using stratified simple random sampling was employed, with data collected from 331 vocational college teachers using a validated questionnaire adapted from the Organizational Culture Inventory (OCI) and the Innovative Work Behaviour Questionnaire (IWBQ). Multiple regression analysis showed that among the four dimensions of Organizational Culture: Innovativeness, Effectiveness, Cooperativeness, and Consistency, Innovativeness recorded the highest standardized beta coefficient (β = 0.522, p < 0.001), making it the most influential predictor of teacher innovation. A follow up simple linear regression revealed that Innovativeness alone explained 27.3 percent of the variance in IWB (R² = 0.273, p < 0.001), representing a large effect size. While Innovativeness had the strongest impact, other cultural dimensions such as Cooperativeness and Consistency demonstrated limited direct influence, suggesting their potential lies in interaction with innovativeness rather than in isolation. In conclusion, the findings provide empirical evidence that fostering innovativeness is vital for equipping teachers to generate, promote, and implement new ideas. Practical implications highlight the need for actionable strategies such as embedding innovation in professional development, incentivising risk taking, fostering cross disciplinary collaboration, and balancing stability with flexibility. These results underscore the importance of embedding innovativeness into institutional culture to ensure that TVET educators remain agile, responsive to industrial changes, and aligned with the objectives of the National TVET Policy 2030